Dot for short - Friedman, Frieda (New York Morrow, 1947)
Dot, a young New York girl who would give anything to be tall, pretty, and self-confident like her two older sisters, becomes a hero during a family crisis.
Keywords: Family life -- Fiction; New York (N.Y.) -- Fiction